Enhancing L2 Motivation and English Proficiency through Technology - Gonzalez Mujico, Flordelis; Lasagabaster, David (Complutense Journal of English Studies, 2019)
Balancing and mastering the linguistic and academic demands of English teaching in higher education can become a difficult hurdle to surpass. Since curricula that integrates technology appears to provide an array of opportunities that promote engagement and language skills, it is worth examining how and whether L2 motivation, self-regulation and learning can be heightened through digital technologies. This paper describes a 6-week intervention programme conducted on 205 international students enrolled on an English for Academic Purposes course at a British university. Based on L2 imagery techniques and ePortfolios, the intervention proved to be of benefit to learner engagement and language acquisition.